2020
DOI: 10.1007/s11133-020-09468-7
|View full text |Cite
|
Sign up to set email alerts
|

Names and Selves: Transnational Identities and Self-Presentation among Elite Chinese International Students

Abstract: What accounts for name choices in a transnational context? What does the choice of ethnic or English names reveal about global identities and the desire to fit into a new culture? Drawing on the sociology of culture and migration, we examine the intersection of naming, assimilation, and self-presentation in light of international student mobility. Based on 25 semi-structured interviews with mainland Chinese students enrolled in an elite Midwestern university, we find that these students make name choices by en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…The most effective way to diversify the field would be by flooding it with a wide range of voices and experiences. Many other compelling studies located in the East Asian context direct our attention to themes such as occupational identities among Korean poets, Chinese painters, and Japanese musicians Zhang 2015;Kowalczyk 2022); galleries, art markets, and the materiality aspect of exhibitions (Zhang 2020(Zhang , 2022; emotions in reality TV shows (Wei 2014); naming culture (Obukhova et al 2014;Fang and Fine 2020); fashion and fast fashion (Zhao 2013; Chu 2018); grassroots branding (Zemanek 2018); the visual arts in the middle-class home (Fang 2018); and local receptions of American television (Gao 2016). As creative cultures continue to emerge and evolve in the region, it is imperative that we expand the scope of empirical studies to incorporate these diverse and exciting experiences.…”
Section: Future Directionsmentioning
confidence: 99%
“…The most effective way to diversify the field would be by flooding it with a wide range of voices and experiences. Many other compelling studies located in the East Asian context direct our attention to themes such as occupational identities among Korean poets, Chinese painters, and Japanese musicians Zhang 2015;Kowalczyk 2022); galleries, art markets, and the materiality aspect of exhibitions (Zhang 2020(Zhang , 2022; emotions in reality TV shows (Wei 2014); naming culture (Obukhova et al 2014;Fang and Fine 2020); fashion and fast fashion (Zhao 2013; Chu 2018); grassroots branding (Zemanek 2018); the visual arts in the middle-class home (Fang 2018); and local receptions of American television (Gao 2016). As creative cultures continue to emerge and evolve in the region, it is imperative that we expand the scope of empirical studies to incorporate these diverse and exciting experiences.…”
Section: Future Directionsmentioning
confidence: 99%
“…Both papers offered critiques of the problematic, colonial nature of media and academic representations of the Chinese international students in the American context. Additionally, an emergent group of empirical work directly engages with the Chinese international students’ racialised experiences, either as victims of neo-racism and the ‘other’ in American colleges (Yao, 2018), or as informed agents of naming practices demonstrating acute racial and ethnic awareness of what names meant for their ethnic identities (Fang & Fine, 2020 ).…”
Section: Subject Positionsmentioning
confidence: 99%
“…However, as numerous surveys, questionaries, interviews, and quantitative studies have suggested, the integration path contains many obstacles, and Chinese international students' level of success in integration is mixed. On the one hand, some students experience successful integration, in which they recognize the importance of preserving their own identities while also accepting the norms of mainstream society [9]. In a qualitative study of the relationship between Chinese international students' use of English names, assimilation, and self-presentation, Fang and Fine argues that for students who dropped their English names, their ethnic names serve as a representation of their unique Chinese identity compared to other groups in the host society [9].…”
Section: Integrationmentioning
confidence: 99%
“…On the one hand, some students experience successful integration, in which they recognize the importance of preserving their own identities while also accepting the norms of mainstream society [9]. In a qualitative study of the relationship between Chinese international students' use of English names, assimilation, and self-presentation, Fang and Fine argues that for students who dropped their English names, their ethnic names serve as a representation of their unique Chinese identity compared to other groups in the host society [9]. Such demonstration can be viewed as a form of successful integration.…”
Section: Integrationmentioning
confidence: 99%
See 1 more Smart Citation